The immortal germline - Lehmann, Ruth (Current topics in developmental biology, 2019)
The Immortal Germline, Volume 135 in the Current Topics in Developmental Biology series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of topics, including Balbiani body, germ plasm and polarity, Wolbachia and the germline, Human germ line biology, Reproduction/immunity and sperm success, Mammalian spermatogenesis, Reproduction/regeneration and germ cells in planarians, Germline stem cell homeostasis, Germline soma interactions/sex determination, Reconstituting the mouse germ-cell specification pathway in vitro, Maternal Germ line inheritance of mitochondria, Transposon strategies, and more.